ANALYZING INDUSTRY 4.0 WITH AN EXAMPLE FROM AGRICULTURAL MANUFACTURING - Turapov, Bahram; Siegfried, Patrick (Accurate: Journal of Mechanical Engineering and Science, 2021)
A study of industry 4.0 technologies in the John Deere and Company and their impact on company operations is presented in this paper. Deere and Company’s implementation of Industry 4.0 to its factories and its factors was the focus of the research. The literature review with the systematic approach as well as a comprehensive review of current John Deere and Company’s developments is used in the current study. Also, it relied on freely available information on the company website. Public and investor relations have also been used as credible sources of information. An analysis found that adopting industry 4.0 technologies to agriculture manufacturing results in higher quality products, increased productivity, safety, and wider acceptance among stakeholders. This study assumes full implementation of these technologies in all agriculture manufacturing companies, and it also emphasizes up-to-date technologies. Studying this topic can be useful for engineers in mechanical and agricultural fields, managers in business, and marketers.